Polyunsaturated Fatty Acid Biosynthesis in Cotyledons from Germinating and Developing Cucumis sativus L. Seedlings - Murphy, Denis J. (1980)
Etiolated Cucumis sativus L. cotyledons preferentially catabolized exogenous [1-(14)C]oleic acid and [1-(14)C]linoleic acid with relatively little incorporation into complex lipids or desaturation of the (14)C-labeled fatty acids. Following a 16-hour exposure to light, the greening cotyledons efficiently desaturated the exogenous (14)C-labeled fatty acids. A small amount of oleate desaturation to linoleate was observed in etiolated tissue, but hardly any linoleate desaturation to α-linolenate was detected. Both oleate and linoleate desaturation showed diurnal variations with maxima at the end of light periods and minima at the end of dark periods. Illumination of etiolated tissue by flashing light, as opposed to continuous light, failed to stimulate either chlorophyll or α-linolenic acid biosynthesis, and both processes could be halted or reversed by 10 micrograms per milliliter cycloheximide. Production of polyunsaturated fatty acids from [1-(14)C]acetate, [1-(14)C]oleic acid, and [1-(14)C]linoleic acid, by greening cucumber cotyledons, was markedly affected by tissue integrity with finely chopped cotyledons having very little capacity for their synthesis and intact seedlings showing the highest rates.